What should dental services for people with disabilities in Ireland be like? Agreed priorities from a focus group of people with learning disabilities. (21st November 2015) - Mac Giolla Phadraig, Caoimhin; Dougall, Alison; Stapleton, Siobhan; McGeown, Danielle; Nunn, June; Guerin, Suzanne
Abstract : Accessible summary: This study asked a group of people with learning disabilities in Ireland what was important to them about their dental services. The group easily ordered their priorities according to five topics: Access, Cost, Information, Quality of Care and Treatment . The group's discussion revealed a disempowered group who had little control over how they interacted with dental services. We suggest ways to empower people with learning disabilities in their interactions with dental services. Abstract: Background: In Ireland, people with learning disabilities have poor oral health. This is in part due to inappropriate oral health services. Recognising the value of inclusive approaches to research and healthcare planning, this study sought to include a group of people with learning disabilities in priority setting for oral health services in Ireland. This study discusses the feasibility of the methods used to promote inclusive approaches in oral healthcare planning. Materials and Methods: A single focus group of six participants with communication and cognitive impairments agreed priorities for dental services using evidence‐based research tools across five topics: Access, Cost, Information, Quality of Care and Treatment . Sorting was recorded photographically and discussion was video‐recorded, transcribed and analysed using deductive content analysis. Results: The group ranked priorities within each topic but found it difficult to meaningfully rank between topics. Across topics, issues of control, empowerment and choice were observed. Conclusions: Participants were largely disempowered in their interactions with dental services. The method used in this study to empower potential service users with disabilities was successful and can be used by others who have an interest in inclusive healthcare priority setting.